2017
DOI: 10.1111/imj.13634
|View full text |Cite
|
Sign up to set email alerts
|

Medication reconciliation at two teaching hospitals in Australia: a missed opportunity?

Abstract: Medication reconciliation prevents medication related harm at patient hospitalisation. This cross-sectional study demonstrated that the Hunter New England Health Admission Medication History Form that supports the two processes is underutilised in two hospitals in New South Wales with many doctors unaware of the form and pharmacists facing understaffing and time constraints for completing it. Triaging of patients and, more collaboration between doctors and pharmacists are required for efficient in-hospital med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
2
6
0
1
Order By: Relevance
“…Nurses reported medication reconciliation at hospital discharge was a complex process involving numerous clinicians who completed similar tasks such as patient education (Penm et al, 2019; Siu, 2015). Confirming previous research (Aires‐Moreno et al, 2020; Athuraliya et al, 2017), nurses in our study identified medication discrepancies, checked the accuracy of discharge medications, delivered patient education, and coordinated the healthcare team to ensure patient safety and avoid discharge delays. Task duplication was considered both a barrier and a benefit in some circumstances.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Nurses reported medication reconciliation at hospital discharge was a complex process involving numerous clinicians who completed similar tasks such as patient education (Penm et al, 2019; Siu, 2015). Confirming previous research (Aires‐Moreno et al, 2020; Athuraliya et al, 2017), nurses in our study identified medication discrepancies, checked the accuracy of discharge medications, delivered patient education, and coordinated the healthcare team to ensure patient safety and avoid discharge delays. Task duplication was considered both a barrier and a benefit in some circumstances.…”
Section: Discussionsupporting
confidence: 85%
“…Prior to hospital discharge, medication reconciliation tasks include reconciling previous and newly prescribed medications; documenting an accurate discharge medication list; prescribing, dispensing and checking discharge medications; patient and carer education; and disseminating medication information to community healthcare professionals involved in the patient's ongoing care (Latimer et al, 2020; Lee et al, 2015; World Health Organisation, 2006). However, evidence suggests more than half of hospital patients do not have their medications reconciled on admission or prior to discharge, which increases their risk of medication‐related harm (Athuraliya et al, 2017; Michaelsen et al, 2015; Stark et al, 2020). A 2015 systematic review of 15 quantitative research papers on medication reconciliation at hospital discharge found between 20–87% of patients had at least one medication discrepancy at discharge, mostly omissions, with polypharmacy increasing the risk for error (Michaelsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time constraints are known to be a recurring barrier to many innovative initiatives and scope‐advancing practices in pharmacy, such as medication reconciliation, vaccination administration, sexual and reproductive health services, continuing education, inclusion in a research network, and general research efforts . Pharmacists expressed concern with the amount of time needed for proper patient education on naloxone, noting that appropriate education on overdose risk, responding to an overdose, and the proper use of naloxone could require a significant time commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Średnia liczba leków przyjmowanych przez pacjenta liczona na podstawie wywiadu lekarskiego wyniosła 6,58. Dla wywiadu koncyliacyjnego była ona większa i wyniosła 8,52 [7]. W innym badaniu, tym razem z Arabii Saudyjskiej, autorstwa Abdulghani i wsp., całkowita liczba leków przyjmowanych przez pacjentów, w przypadku informacji uzyskanej przez osobę prowadzącą koncyliację wyniosła 3085, a przez lekarza -2548 [8].…”
Section: śWiadomość Lekowa Pacjentówunclassified